2010
DOI: 10.1118/1.3292633
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound B‐scan image simulation, segmentation, and analysis of the equine tendon

Abstract: To conclude, this technique may provide a tool for the rapid assessment and characterization of tendon structures to enable clinical identification of the integrity of the SDFT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that fascicle cross section within the equine SDFT appears irregular [46] such that assuming a circular cross section may lead to errors when calculating the stress to apply during FL. This may partially account for the larger variation seen in the microstructural strain response in fatigue-loaded samples.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that fascicle cross section within the equine SDFT appears irregular [46] such that assuming a circular cross section may lead to errors when calculating the stress to apply during FL. This may partially account for the larger variation seen in the microstructural strain response in fatigue-loaded samples.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the inter-collagen-bundle space in the SDFT, which contains interfascicular space and interfibrillar space, ranged between 1 and 80 μm. If the thickness of the inter-collagen-bundle space is larger than the wavelength (approximately 54 μm at 30 MHz), strong echoes are acquired from the space, and no specific structures can be observed for the thickness of an inter-collagen-bundle smaller than the wavelength [ 59 ]. Hence, a greater thickness in the inter-collagen-bundle space of the SDFT compared with the A1 pulley would lead the SDFT to have higher backscattering intensity.…”
Section: Discussionmentioning
confidence: 99%